Allometry in carcasses of lambs of the Pantaneiro genetic group slaughtered with different subcutaneous fat thickness - Natália Holtz Alves Pedroso Mora; Francisco de Assis Fonseca de Macedo; José Carlos Silveira Osório; Elias Nunes Martins; Alexandre Agostinho Mexia; Thiago Gomes de Macedo (Acta Scientiarum. Animal Sciences, 2014)
Twenty-four female lambs of the Pantaneiro genetic group, with approximately 100 days of age, average body of 16.24 ± 1.78 kg, were slaughtered with 2.0, 3.0 and 4.0 mmof subcutaneous fat thickness, measured by ultrasound in the Longissimus, to evaluate the allometric growth. Lambs fed a complete pelleted diet calculated to ensure a daily weight gain of0.30 kg. Slaughtering was performed as the female lambs reached the pre-established fat thickness. After 24 hours in a cold chamber at 4ºC, chilled carcasses were cut in half and weighed. The right side was separated into five sections to determine the allometry of carcasses and cuts. Neck and rib showed isogonic growth in all treatments. Loin has remained late growth to 2.0 and3.0 mm. Shoulder and leg were isogonic growth in the treatments 3.0 and4.0 mm. The leg in relation to half carcass showed the greatest correlation. The cuts exhibited differentiated development in the growth rates of tissues. It is recommended to slaughter female lambs when they reach3.0 mm of subcutaneous fat thickness, since the carcass has already reached physiological maturity. Shoulder and leg cuts are best suited for dissection for presenting the highest correlation with the carcass in females of the Pantaneiro group.